Improving English Pronunciation Skills through AI-Based Speech Recognition Technology - Dja'far, Veri Hardinansyah; Hamidah, Fitria Nur (Universitas Cokroaminoto Palopo, 2024)
This research examines the effectiveness of AI-based speech recognition technology in fostering English pronunciation skills among students. The study emphasizes the importance of pronunciation proficiency as a cornerstone of language learning and its impact on overall communication effectiveness. A quasi-experimental design with a pretest-posttest control group methodology was employed. The participants were 58 third-year Accounting Diploma students from State Polytechnic of Malang, Indonesia. They were divided into two groups: an experimental class utilizing the Google Read Along application and a control class receiving conventional teaching methods. The results demonstrate a significant improvement in pronunciation skills within the experimental group. These students achieved an average N-Gain score of 0.7646, categorized as